Planificación y optimización de un operador móvil virtual como unidad de negocio para la infraestructura de medición avanzada de energía eléctrica - Guevara Ortiz, Leandro Alcívar (2014)
Warn of a performance management system that links smart metering at a distribution company through the use of telecommunications under the concept of virtual mobile operator, applied to the measurement infrastructure advanced (AMI), the work has come from experiences in other countries and the particular situation, to consider the feasibility of implementing.